Pengaruh Live Commerce dan Payment Convenience terhadap Impulse Buying dengan Trust sebagai Variabel Intervening (Studi Kasus pada Pengguna Tiktok Shop di Kabupaten Pati) - Shodiqi, Muhammad Haris; Mulyana, Mulyana (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of Live Commerce and Payment Convenience on Impulse Buying, with Trust as an intervening variable among TikTok Shop users in Pati Regency. This study used a quantitative approach, collecting data through questionnaires distributed to 100 respondents. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests and F-tests, and the Sobel Test to examine the role of intervening variables. The results showed that Live Commerce and Payment Convenience had a positive and significant effect on Trust. Furthermore, Live Commerce, Payment Convenience, and Trust were also shown to have a positive and significant effect on Impulse Buying. The Sobel Test results showed that Trust significantly mediated the relationship between Live Commerce and Payment Convenience on Impulse Buying. These findings indicate that building consumer trust is a crucial element in encouraging impulsive buying behavior on the TikTok Shop platform.